2013
DOI: 10.1056/nejmoa1208024
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII Products and Inhibitor Development in Severe Hemophilia A

Abstract: Recombinant and plasma-derived factor VIII products conferred similar risks of inhibitor development, and the content of von Willebrand factor in the products and switching among products were not associated with the risk of inhibitor development. Second-generation full-length recombinant products were associated with an increased risk, as compared with third-generation products. (Funded by Bayer Healthcare and Baxter BioScience.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
476
10
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(525 citation statements)
references
References 33 publications
29
476
10
10
Order By: Relevance
“…Some studies have shown that patients treated with second-generation rFVIII products presented a higher risk of inhibitor development when compared with third-generation products. [9][10][11] FVIII inhibitor is an immunoglobulin G (IgG) produced by patient that has high polyclonal affinity directed against the FVIII protein. 12 Inhibitory antibodies are directed usually against the A2, A3 and C2 FVIII domains.…”
Section: Recombinant Factor VIII Productsmentioning
confidence: 99%
“…Some studies have shown that patients treated with second-generation rFVIII products presented a higher risk of inhibitor development when compared with third-generation products. [9][10][11] FVIII inhibitor is an immunoglobulin G (IgG) produced by patient that has high polyclonal affinity directed against the FVIII protein. 12 Inhibitory antibodies are directed usually against the A2, A3 and C2 FVIII domains.…”
Section: Recombinant Factor VIII Productsmentioning
confidence: 99%
“…It seems, we are experiencing a similar question following a recent report on differences in immunogenicity between various factor VIII (FVIII) concentrates in patients with haemophilia A [1]. The report provided incidences of the development of neutralizing antibodies (inhibitors) against FVIII -a severe side effect of the treatment with FVIII -according to product brands.…”
mentioning
confidence: 96%
“…The RODIN report clearly describes all eligible patients and exclusions with the reasons for exclusion in Fig. 1, and very few data were missing [1]. In the Supplementary material [1] on missing data we read, 'In 12.4% of patients, the F8 gene mutation type was missing.…”
mentioning
confidence: 99%
See 2 more Smart Citations